The mechanism of action of paeoniae radix rubra–angelicae sinensis radix drug pair in the treatment of rheumatoid arthritis through PI3K/AKT/NF-κB signaling pathway - Li, Jia; Zhang, Xiaofei; Guo, Dongyan; Shi, Yajun; Zhang, Shihao; Yang, Ruiying; Cheng, Jiangxue (Frontiers in Pharmacology, 2023)
Objective: To investigate the effects and mechanisms of Paeoniae radix rubra–Angelica sinensis radix (P-A) drug pair in the treatment of rheumatoid arthritis (RA). Methods: Mass spectrometry was employed to accurately characterize the main components of the P-A drug pair. Network pharmacology was used to analyze the main components and pathways of the P-A drug pair in the treatment of RA, and Discovery Studio software was used to molecularly dock the key proteins on the pathway with their corresponding compounds. The levels of serum TNF-a, IL-1β, and IL-6 were measured by enzyme linked immunosorbent assay (ELISA). The histopathology of the ankle joint was observed by hematoxylin-eosin (HE) staining, and the positive expression of p-PI3K, p-IKK, p-NF-κB, and p-AKT in the synovial tissue of the ankle joint was detected by immunohistochemical analysis. Finally, the expression of PI3K, IKK, and AKT and their phosphorylation levels were determined by Western blot in each group of rats. Results: Network pharmacology combined with molecular docking analysis revealed that the pharmacodynamic mechanism of the P-A drug pair for the treatment of RA may be related to the contents of caffeic acid, quercetin, paeoniflorin, and baicalein in the regulation of the expression of the PI3K/AKT/NF-κB signaling pathway and the targets of PIK3CA, PIK3R1, AKT1, HSP90AA1 and IKBKB in the pathway. Compared with the model group, the P-A drug pair significantly improved the pathological changes of the synovial tissue and reduced foot swelling in RA model rats. Moreover, it regulated the levels of TNF-α, IL-1β, and IL-6 in serum (P < 0.05). The results of the immunohistochemical analysis and Western blot showed that the expression of PI3K, IKK, NF-κB, and AKT decreased after phosphorylation in the synovial tissue (P < 0.05). Conclusion: The P-A drug pair exhibited an inhibitory effect on the hyperactivation of the PI3K/AKT/NF-κB signaling pathway in the synovial membrane of RA rats. The mechanism may be related to the downregulation of the phosphorylation levels PI3K, IKK, NF-κB, and AKT, which in turn decreased inflammatory cell infiltration and synovial membrane proliferation.